Preservation of Facial Nerve Function Repaired by Using Fibrin Glue-Coated Collagen Fleece for a Totally Transected Facial Nerve during Vestibular Schwannoma Surgery - Choi, Kyung-Sik (The Korean Neurosurgical Society, 2014)
Recently, the increasing rates of facial nerve preservation after vestibular schwannoma (VS) surgery have been achieved. However, the management of a partially or completely damaged facial nerve remains an important issue. The authors report a patient who was had a good recovery after a facial nerve reconstruction using fibrin glue-coated collagen fleece for a totally transected facial nerve during VS surgery. And, we verifed the anatomical preservation and functional outcome of the facial nerve with postoperative diffusion tensor (DT) imaging facial nerve tractography, electroneurography (ENoG) and House-Brackmann (HB) grade. DT imaging tractography at the 3rd postoperative day revealed preservation of facial nerve. And facial nerve degeneration ratio was 94.1% at 7th postoperative day ENoG. At postoperative 3 months and 1 year follow-up examination with DT imaging facial nerve tractography and ENoG, good results for facial nerve function were observed.